2007
DOI: 10.1002/hep.21816
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis delta in Europe: Vanishing or refreshing?

Abstract: We thank Dr. Targher, Dr. Manco, and their colleagues for their interest in our work. Both groups of investigators suggest that the existing literature and our observations regarding the correlation between the presence of dorsocervical lipohypertrophy (DCL) and severity of nonalcoholic steatohepatitis (NASH) indicate a dysfunction of the hypothalamic-pituitary axis (HPA). We completely agree with this assessment and had indeed suggested that this possibility should be systematically evaluated. 1 Although we a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 10 publications
3
29
0
2
Order By: Relevance
“…In a recent survey of 1,136 HBsAg carriers recruited in Italy in the beginning of the current decade, the prevalence of anti-HD among carriers of the HBsAg was 9.7% [22] , which is similar to the prevalence found in 1997.…”
Section: Current Scenario In Europementioning
confidence: 52%
“…In a recent survey of 1,136 HBsAg carriers recruited in Italy in the beginning of the current decade, the prevalence of anti-HD among carriers of the HBsAg was 9.7% [22] , which is similar to the prevalence found in 1997.…”
Section: Current Scenario In Europementioning
confidence: 52%
“…However, since the survey of 2006 [12], the prevalence has become higher in the latter ones. This evolving geographical pattern may reflect changes in the modes of transmission.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the present findings have been compared with the corresponding figures from the previous studies [8][9][10][11][12] to detect changes, if any.…”
Section: Introductionmentioning
confidence: 94%
“…Several reports suggest that the increasing awareness of the risk of transmitting AIDS, universal vaccination campaigns against HBV, and improvements in socioeconomic conditions have contributed to a decrease in the incidence of HBV infection and, consequently, a decrease in the spread of HDV infection. On the other hand, it was reported that this downward prevalence trend has stopped, most likely as a consequence of resurgent drug addiction and other independent risk exposures [50]. The geographic distribution of HDV infection is not a simple refl ection of distribution of HBV infection.…”
Section: Epidemiologymentioning
confidence: 96%